2004
DOI: 10.1002/ctpp.200410037
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Ionization Rate in the Scrape‐off Layer

Abstract: The purpose of this work is to study the effect of multi-step ionization on the tokamak scrape-of layer (SOL). Using particle-in-cell (PIC) simulations we show that this effect strongly influences the divertor plasma. Our results suggest that, at least for high-recycling regimes, multi-step ionization should necessarily be included in SOL analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…Qualitatively similar effects of kinetics on temperature profiles as those shown in figures 3 and 4, with upstream temperatures rising and downstream falling, were found in earlier kinetic calculations, for example in the particle in cell (PIC) code modelling, when comparing them to fluid code calculations, see figure 6 in [7]. Figure 5 shows T e , n e , and total, ion plus electron, conductive plus convective, parallel power flux profiles to divertor targets for EDGE2D-EIRENE iterations 0 and 5.…”
Section: Setup Of Edge2d-eirene Cases and Kipp-edge2d Iterative Couplingsupporting
confidence: 76%
See 1 more Smart Citation
“…Qualitatively similar effects of kinetics on temperature profiles as those shown in figures 3 and 4, with upstream temperatures rising and downstream falling, were found in earlier kinetic calculations, for example in the particle in cell (PIC) code modelling, when comparing them to fluid code calculations, see figure 6 in [7]. Figure 5 shows T e , n e , and total, ion plus electron, conductive plus convective, parallel power flux profiles to divertor targets for EDGE2D-EIRENE iterations 0 and 5.…”
Section: Setup Of Edge2d-eirene Cases and Kipp-edge2d Iterative Couplingsupporting
confidence: 76%
“…In the iterative KIPP-EDGE2D-EIRENE modelling described here non-Maxwellian features of the electron distribution function in the calculation of rate constants for atomic physics processes contributing to particle and power sources were not taken into account, despite a significant impact of high energy tail electrons on the rates in the divertor was reported (see e.g. [7,[9][10][11]). The main trends in adding kinetic atomic rates to fluid code plasma solutions in high recycling plasmas are summarized in [12], where 1% population of high energy super-thermal electrons was artificially added to SOLPS (a 2D edge fluid code) modelling into detached divertor plasma.…”
Section: Power Balance In Kipp-edge2d Solutionsmentioning
confidence: 99%
“…Due to the presence of high energy non-Maxwellian tails of the electron distribution function, f e , near the target, kinetic rates of interaction between electrons and neutrals and impurities may increase by a large factor (see e.g. [10][11][12][13]). Such effects are, however, outside of the scope of the present paper, in which the emphasis is put on the ability of superthermal electrons to create substantial deviations of the electron heat conduction from predictions based on the classical Braginskii formula, and their impact on heat transmission factors γ e at the divertor target.…”
Section: Introductionmentioning
confidence: 99%
“…The rate coefficients for atomic physics from ADAS, calculated based on the collision-radiative theory [52,53] with assuming Maxwellian electrons, are tabulated and then read as an input file in SOLPS. Previous studies [28,54,55] showed that the extended non-Maxwellian tail downstream near the target had substantial effects on enhancing the deuterium ionization rate coefficient. Particularly when electron temperature was lower than 3eV , the presence of small amount (1%) of hot electrons (20eV ) could contribute significantly to the local ionization rate coefficient [56].…”
Section: Kinetic Effects On Deuterium Ionizationmentioning
confidence: 99%